The Russian Civil War, 1918-1921 : an operational-strategic sketch of the Red Army's combat operations - Bubnov, A. (Andreĭ); Harrison, Richard W. (Casemate Academic, 2020)
"A wealth of knowledge. . .For every incident, chasing Kornilov or dealing with Admiral Kolchak, the reader has a 360-degree view." -- Roads to the Great War The Russian Civil War was one of the most fateful of the 20th century's military conflicts, a bloody three-year struggle whose outcome saw the establishment of a totalitarian communist.